Color as a Catalyst in Junk Food Marketing: A Social Semiotic Perspective - Hameed, Assistant. Lecturer. Duaa Fareed; Al-Zubaidy, Assistant. Lecturer. Fatima Hussein (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2025)
Social semiotics has emerged as a framework for understanding how meaning is created, communicated, and interpreted within various social and cultural contexts. Kress and van Leeuwen (2006) aim to provide readers with a clear set of analytical tools for conducting social semiotic analyses. This study focuses on exploring the role of color as a catalyst in junk food marketing. The data for this analysis is collected from the official websites of junk food restaurant posters, including Pizza Hut, KFC, McDonald’s, Subway, and Wendy’s. Additionally, colors positively influence customers’ feelings and moods. Therefore, this study sets out to explore and address the following crucial questions: (1) What psychological effects do colors have on community behavior? (2) How does color contribute to the structure and emphasis of the marketing message?